The Effect of Giving PMT Combination of Mung Bean Porridge and Boiled Eggs on Changes in Weight and Height of Stunting Toddlers at the Barong Tongkok Health Center - Margaritha Sustanti; Umi Kalsum; Nursyahid Siregar (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effect of giving supplementary food (PMT) a combination of mung bean porridge and boiled eggs on changes in weight and height status in stunting toddlers. The design of this research is quasi-experimental using the one group pretest-posttest design model. The population in this study were toddlers who came to visit the Barong Tongkok Health Center from September to November 2021 with a total of 67 toddlers. Sampling in this study using purposive sampling technique and obtained as many as 18 respondents. Data analysis techniques using paired t-test to determine the effect between variables. The results of the hypothesis test obtained a p-value of 0.000 (<0.05) so that there was an effect of giving PMT on the BB of stunting toddlers, while a ¬p-value was obtained of 0.390 (>0.05) so that there was no effect of giving PMT on height of stunting toddlers.